Peran Guru Penggerak dalam Implementasi Kurikulum Merdeka Pada Jenjang SMA di Kota Depok - Sari, Ani Nurinda; Sunarya, Yaya (Universitas Indraprasta PGRI, 2023)
This study aims to examine the role of the driving teacher in implementing the independent curriculum at the senior high school level in Depok City. This research is a qualitative descriptive research. Data collection was carried out using literature study and interview methods. Driving teacher education is a leadership education program for teachers to become learning leaders. This program includes online training, workshops, conferences, and six months of mentoring for prospective driving teachers. During the program, the teacher continues to carry out his teaching duties as a teacher. The role of the driving teacher includes encouraging student growth and development holistically (Pancasila student profile), becoming a trainer (coach/mentor) for other teachers for student-centered learning, being a role model and agent of transformation for the education ecosystem. The results of this study indicate that driving teachers must be able to become independent teachers who are not only trapped in the content of the independent curriculum, but rather in practical and innovative applications so that the goals of implementing the independent curriculum are truly achieved.